Lupus and Lymphoma: An Intriguing Association - Saurabh Gupta; Rajesh Chetiwal; Poonam Gupta; Priyank Rastogi; Amit Kumar (Indian Journal of Medical Specialities)
A 21-year-old female patient, diagnosed with systemic lupus erythematosus (SLE) without renal involvement on remission with oral corticosteroids and hydroxychloroquine for the past 6 months. presented again with a history of polyarthralgia, weight loss, high-grade fever, and neck swelling. Histological and radiological studies confirmed non-Hodgkin's lymphoma subtype diffuse large B-cell type. We thus report an infrequent and intriguing association of non-Hodgkin's disease with SLE. The awareness of the association of non-Hodgkin's disease with SLE and its modes of presentation will help in the early diagnosis and management of such patients.